Concept Mapping Strategy: An Effective Tool for Improving Students' Academic Achievement in Biology - John Sakiyo; Kawu Waziri (Seyit Ahmet Kıray, 2015)
The study investigated the use of concept mapping teaching method on secondary school students' academic achievement in biology. Two hypotheses tested at 0.05 level of significance guided the study. The design of the study was quasi-experimental design with 122 Senior Secondary students selected purposively from two senior secondary schools in Adamawa state. Instrument used for data collection was an achievement test tagged Biology Students' Achievement Test (BSAT) adapted from WAEC tests 2005 to 2010. The instrument was content validated by three experts and Cronbach alpha formula was used for testing its reliability. The reliability coefficient of 0.78 was obtained. The treatment lasted for six weeks and data were analyzed using one-way Analysis of Covariance (ANCOVA). The result revealed that, concept mapping method enhanced students' academic achievement in biology. Furthermore, there was no significant difference between male and female students in the experimental group. It was recommended that, concept mapping method should be incorporated in the teaching of biology for meaningful learning and that workshops should be organized for in-service and practicing teachers on how to use concept mapping strategy.